ON NO-TILL TECHNOLOGY FOR IMPROVING THE FERTILITY OF STONE-GRAVEL SOILS (Scientific journal of the Fergana State University, 2025)
In this article, it is stated that with the help of no-till technology, restoring the soils to a quality condition for cultivation, using foreign experience in areas where wind and water erosion is developed, without saline is a high efficiency and expanding its area is a modern requirement.